A Manager's Role in Obtaining a Fair Day's Work for a Fair Day's Pay—Part II - Derek Farnsworth; Jennifer Clark; Allen F. Wysocki; Karl W. Kepner (EDIS)
This document explores the role of managers in ensuring associates deliver a fair day’s work for a fair day’s pay.  The article discusses eight agree/disagree statements to highlight common management beliefs and their impact on motivation and performance. Part 2.